Transient Modelling of Pumped Two-Phase Cooling Systems: Comparison between experiment and simulation with R134a - Gerner, H.J. van; Bolder, R.; Es, J. van (My University, 2017)
Two-phase pumped cooling systems are applied when it is required to maintain a very stable temperature in a system, for example in the AMS02, which was launched with a space shuttle (in May 2011) and subsequently mounted on the International Space Station. However, a two-phase pumped cooling system can show complex transient behavior in response to heat load variations. For example, when the heat load is increased, a large volume of vapor is suddenly created, which results in a liquid flow into the accumulator and an increase in the pressure drop. This will result in variations in the temperature in the system, which are undesired. It is necessary to calculate these temperature variations before an application is being built. For this reason, a software tool for transient two-phase systems has been developed by NLR. This tool numerically solves the one-dimensional time-dependent compressible Navier-Stokes equations, and includes the thermal inertia of all the components. In this paper, the numerical results from the model are compared to experimental results obtained with the NLR two-phase test facility with R134a as refrigerant.